Effect of Medicinal Herbs in the Treatment of Thyroid Malignancy - Zoleikha Azari; Bahman Jalali Kondori; Mohammad Hossein Asadi (Negah Institute for Scientific Communication, 2019)
Thyroid cancer is the most common endocrine malignant tumor, and its incidence is on the rise. A survey conducted by the Iranian Cancer Institute showed that thyroid cancer constitutes 1.8% of all cancers and 76.1% of endocrine cancers. A lot of studies are being conducted in order to prevent, alleviate pain, and treat cancer using medicinal herbs. Medicinal herbs are important sources of, and rich in, natural antioxidants. There is lots of evidence that some herbal compounds such as vitamins, flavonoids, polyphenols, carotenoids, and herbal steroids have anticancer properties and can act as mutagenic inhibitors. In this review article, first, prevalence and characteristics of thyroid cancer will be examined. Then, a variety of compounds contained in the plant extracts, which have anticancer properties, and methods of extracting plant extracts will be investigated. Moreover, a number of studies which investigated the impact of medicinal herbs on the thyroid malignancy will be reviewed.